She'll Be ‘Right… but Are They? An Australian Perspective on Women in High Performance Sport Coaching - Roberts, Alexandra H.; Clarke, Anthea; Fox-Harding, Caitlin; Askew, Georgia; MacMahon, Clare; Nimphius, Sophia (Frontiers in Sports and Active Living, 2022)
Participation and media coverage of women in high-performance sport has been steadily increasing in recent years throughout the world. While this increase in interest has led to many young women and girls becoming involved in grassroots sport, there has yet to be a significant change in the number of women in coaching roles, particularly at the high-performance level. This paper synthesizes and summarizes the current challenges facing women sport coaches in Australia, drawing from existing research, media and government reports to understand the barriers for women entering and progressing in these roles. We also present some of the more recent initiatives to increase opportunities for women in high performance coaching. Within Australia, there is a need to (1) understand the pipeline for women coaches, (2) examine the interacting contexts and constraints that women are subject to within sporting organizations, and (3) create a preliminary framework for future research, outreach, and education to address gender inequity within Australian sport coaching.